Firms and skills: The evolution of worker sorting - Christina Håkanson; Erik Lindqvist; Jonas Vlachos (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
We document a significant increase in the sorting of workers by cognitive and non-cognitive skills across Swedish firms between 1986 and 2008. The weight of the evidence suggests that the increase in sorting is due to stronger complementarities between worker skills and technology. In particular, a large fraction of the increase can be explained by the expansion of the ICT sector and a reallocation of engineers across firms. We also find evidence of increasing assortative matching, in the sense that workers who are particularly skilled in their respective educational groups are more likely to work in the same firms. Changes in sorting pattens and skill gradients can account for a about half of their increase in between-firm dispersion.
Keywords: J24; J62; L21; O33; 330; skill sorting; skilled-biasedtechnologicalchange; outsourcing; globalization; cognitiveskills; non-cognitiveskills; personality; employer-employeematched data